Pink Tide 2.0: Kebangkitan Kembali Sayap Kiri Amerika Latin Dan Tantangan Di Masa Depan - Jason Fernando; Abharina Nasution; Daniella Wehelmien Salmun; Jeremy Bryce Lim; Maxi Leinderd (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This research aims to explain that left-wing groups have returned to political participation in the Latin American region, which has given birth to the Pink Tide 2.0 phenomenon. The rise of the Pink Tide 2.0 phenomenon began with Mexico in 2018 and Argentina in 2019. This trend continued throughout 2021 and 2022, when many left-wing leaders won elections in Latin America; including Bolivia, Peru, Honduras, Chile, Colombia and Brazil. Elements of the political movement like its predecessor were characterized as "anti-American" and prioritized social-based development, but had a new transformation that focused on environmental protection and fighting climate change, realizing social justice for every race, gender political emancipation (feminism and LGBTQ+), as well as sustainable economic restructuring to eradicate poverty and inequality. This research uses qualitative methods with literature study, as well as social developmentalism theory according to Lena Lavinas. This research concludes that Pink Tide 2.0 emerged due to Latin American society's distrust of right-wing leaders, because they saw stagnant development and increasingly massive inequality following the worsening of the regional economy during the 2010s and the Covid-19 pandemic. Pink Tide 2.0 is the rise of left-wing regimes in Latin America to involve broader segments of society in the sustainable development of each sector.